Short- and long-term effects of brain death on post-transplant graft function in a rodent model - Li, Shiliang; Korkmaz-İçöz, Sevil; Loganathan, Sivakkanan; Radovits, Tamás; Hegedűs, Péter; Karck, Matthias; Szabó, Gábor (Interactive cardiovascular and thoracic surgery, 2015)
Heart transplantation has become the most effective treatment for end-stage heart failure. Donors after brain death (BD) are currently the only reliable source for cardiac transplants. However, haemodynamic instability and cardiac dysfunction have been demonstrated in brain-dead donors and this could therefore also affect post-transplant graft function. We studied the effects of BD on cardiac function and its short-term (1 h) or long-term (5 h) impacts on graft function.
Advance access publication 11 December 2014
Gesehen am 22.06.2020